The Qualification Issue Of The Svanetian Language On The Pages Of The Newspaper “Iveria” - Tedoradze, Marika (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
In scientific literature the qualification issue of Kartvelian languages and dialects is an actual topic. In particular the debates refer to determining the qualification of Mengrelian and Svanetian languages: they are considered either as independent languages or they are assigned the status of dialects and are placed among other dialects of the Georgian languge. Different qualifications of the Georgian speech units originate from the 2nd part of the 19th century. This issue was given the significant attention by the press of that time. The article discusses the debate in the newspaper “Iveria” about the qualification of Svanetian speech. The newspaper “Iveria” was issued in Tbilisi 1877-1906. In different times its editors were I. Tchavtchavadze, S. Meskhi, I. Machabeli, Gr. Kifshidze… The newspaper broadly highlighted the issues of domestic and foreign politiccs. Different publications reveal the interesting viewpoints about the qualification issue of Svanetian speech. According to the materials found in the newspaper “Iveria” activities focusing on the destruction of the national unity of Georgians need proper interest: provocative endeavors of creating Svanetian alphabet; initiation of conducting the church services in Svanetian language. The newspaper used to actively publish the letters of B. Nijaradze, I. Margiani, K. Gelovani. O. Dadeshkeliani, Iv. Margiani, etc. From the materials discussed in the newspaper “Iveria” the qualification of the Svanetian speech was very active in the 2nd part of the 19th century: Russian officials used to assert that Svanetian was the independent language and had nothing common with the Georgian, the Georgian public men resisted those ideas with concrete arguments and insisted that Svanetian language is the Georgian language and there is only one “home language” for Georgians.